Special Allocation Funds (Dak) & Regional Original Income (Pad): How to Manage and Economic Growth in Bandung Regency - Ricky Agusiady (Enrichment : Journal of Management, 2021)
Over time, regional development plans have experienced several problems and obstacles, which are in fact very contrary to the objectives of regional autonomy being proclaimed by the central government, which among others have the aim of creating independence, delegation of authority, exploring the potential of regional government resources so that they are well established. financially. However, not all local governments are financially secure. Seeing several phenomena shows that the financial performance of each local government is different. This can be seen from the increase in regional original income but not followed by an increase in regional spending. This study uses a descriptive study method with a quantitative approach and data triangulation analysis, the results of the study explain that, certain regional financial management can be reflected in the Regional Revenue and Expenditure Budget (APBD) owned by each region, so that it can be used as an instrument to create regulations for regional development. local government. Increasing the allocation of capital expenditure in the form of fixed assets which includes infrastructure, equipment, facilities and infrastructure is very important to increase economic productivity because the higher the capital expenditure, the higher the productivity of the economy. Therefore, the existence of regional autonomy is very influential on the economic growth of a region because it gives freedom to local governments to make their own financial plans and make strategic policies that can affect the progress of the region.